2015
DOI: 10.2147/mder.s57281
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and statistical methods for the prediction of maximal oxygen uptake: recent advances

Abstract: Maximal oxygen uptake (VO2max) indicates how many milliliters of oxygen the body can consume in a state of intense exercise per minute. VO2max plays an important role in both sport and medical sciences for different purposes, such as indicating the endurance capacity of athletes or serving as a metric in estimating the disease risk of a person. In general, the direct measurement of VO2max provides the most accurate assessment of aerobic power. However, despite a high level of accuracy, practical limitations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Predictor Due to fact that SVM [18], in the literature, has been often reported to be superior to other machine learning methods especially in the field of sport physiology [1,19,20], it has been chosen to build the VO 2 max prediction models. SVM constructs a hyperplane or set of hyperplanes in a high-or infinite-dimensional space to perform a regression analysis.…”
Section: Modelsmentioning
confidence: 99%
“…Predictor Due to fact that SVM [18], in the literature, has been often reported to be superior to other machine learning methods especially in the field of sport physiology [1,19,20], it has been chosen to build the VO 2 max prediction models. SVM constructs a hyperplane or set of hyperplanes in a high-or infinite-dimensional space to perform a regression analysis.…”
Section: Modelsmentioning
confidence: 99%
“…When it comes to comparing linear and nonlinear models with regard to prediction accuracy, the quality of prediction of neural models seems to be similar to that of regression analysis and regression models, potentially even better. This seems to hold true in VO 2 max prediction (Abut, & Akay, 2015;Akay, Zayid, Aktürk, & George, 2011) as well as in performance prediction studies (Edelmann-Nusser, Hohmann, & Henneberg, 2002;Maszczyk, Zajac, & Ryguła, 2011;Maszczyk, Rocznoik, Waskiewicz, Czuba, Mikolajec, Zajac, & Stanula, 2012). Hence, Jäger, Kurz and Müller (2016) assume that nonlinear neural network approaches possibly provide more sophisticated methods for predicting maximal mean speed in a 4x1000 m Field Test which may enhance the accuracy of their linear model.…”
Section: Introductionmentioning
confidence: 97%
“…Besides those studies which measure VO 2 max directly in a maximal incremental exercise test on a treadmill or cycle ergometer, there are also some approaches that try to predict VO 2 max based on non-exercise and submaximal exercise test data (e.g., Black, Vehrs, Fellingham, George & Hager, 2016) or even based on statistical models using solely non-exercise data (see Abut & Akay, 2015, for a review). In case of non-exercise models, variables such as sex, age or body mass index were used to predict VO 2 max.…”
Section: Introductionmentioning
confidence: 99%
“…Using inputs with known outputs, it can be trained and then utilized to predict unknown outputs. A 2015 review by Akay et al identified a variety of studies that attempted to use ANNs or other forms of machine learning to predict VO 2 max from maximal, submaximal, and non-exercise data [3]. Additionally, many studies have used ANNs to predict energy expenditure from accelerometer data [15,28,40,41,45].…”
Section: Introductionmentioning
confidence: 99%